Quo vadis edukacjo, czyli czy sztuczna inteligencja może zwolnić nas z myślenia? = Quo vadis education, or can artificial intelligence free us from thinking? - Oleksiuk, Marcin; Szastaj, Paulina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article addresses issues related to the role of artificial intelligence in education, as well as its use in the context of critical thinking and its future in teaching. It is an attempt to present the machine thinking model, which is based on mathematical algorithms, and compare it with the consciousness-based thinking process of humans. One very important aspect of the article is that, in addition to analysing the subject matter, it uses answers generated by Chat GPT, a publicly available tool that uses AI to generate answers to questions.
Keywords: artificial intelligence; AI; education; critical thinking; learning; sztuczna inteligencja; edukacja; myślenie krytyczne; nauka